Photon Dose Enhancement Ratio at the Transition Region of Dissimilar Media - Al-Arif, Maan S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
Accurate measurement was carried out for the dose gradient in Teflon irradiated with filtered X-ray spectra having effective energies of 40 keV and 55 keV when in contact with aluminum, titanium, copper, and tin. At low photon energies, the interface region is only extended for about 10 microns from the interface, therefore, ultra-thin LiF/Teflon discs of the order of 3 microns thick was developed and used to measure directly the dose gradient in Teflon. Due to the relatively large slope of the depth dose curves near the interfaces, a displacement correction factor was introduced to determine the effective measuring point of the detector. A fitting exponential formula is suggested and used to estimate the dose gradient for Bone-Teflon interface. The interface dose for Bone-Teflon is 3.8 times the equilibrium dose at 70 KV, while it is about 3.1 at 100 KV.